The Effect of Gradual Fluorination on the Properties of FnZnPc Thin Films and FnZnPc/C60 Bilayer Photovoltaic Cells. (6th February 2015) - Brendel, Michael; Krause, Stefan; Steindamm, Andreas; Topczak, Anna Katharina; Sundarraj, Sudhakar; Erk, Peter; Höhla, Steffen; Fruehauf, Norbert; Koch, Norbert; Pflaum, Jens
Abstract : Motivated by the possibility of modifying energy levels of a molecule without substantially changing its band gap, the impact of gradual fluorination on the optical and structural properties of zinc phthalocyanine (F n ZnPc) thin films and the electronic characteristics of F n ZnPc/C60 ( n = 0, 4, 8, 16) bilayer cells is investigated. UV–vis measurements reveal similar Q‐ and B‐band absorption of F n ZnPc thin films with n = 0, 4, 8, whereas for F16 ZnPc a different absorption pattern is detected. A correlation between structure and electronic transport is deduced. For F4 ZnPc/C60 cells, the enhanced long range order supports fill factors of 55% and an increase of the short circuit current density by 18%, compared to ZnPc/C60 . As a parameter being sensitive to the organic/organic interface energetics, the open circuit voltage is analyzed. An enhancement of this quantity by 27% and 50% is detected for F4 ZnPc‐ and F8 ZnPc‐based devices, respectively, and is attributed to an increase of the quasi‐Fermi level splitting at the donor/acceptor interface. In contrast, for F16 ZnPc/C60 a decrease of the open circuit voltage is observed. Complementary photoelectron spectroscopy, external quantum efficiency, and photoluminescence measurements reveal a different working principle, which is ascribed to the particular energy level alignment at the interface of the photoactive materials. Abstract : The impact of gradually fluorinated zinc phthalocyanine molecules on the photophysical properties of F n ZnPc/C60 solar cells is investigated. Upon increasing fluorination, distinct variations of the cell parameters such as the open circuit voltage are observed. By combining complementary structural and electron spectroscopy analyses, this yields a detailed picture of the relevant D/A interface energetics and processes on microscopic length scales.